Adaptabilitas Kepala Sekolah Dalam Pemenuhan Kompetensi Sebagai Kepala Sekolah Studi Fenomenologi Guru Penggerak menjadi Kepala Sekolahdi Taman Kanak-Kanak Negeri Jakarta Selatan Wilayah I - Laila Sari Ramadhan; Nurhatatti Nurhatatti; Kamaludin Kamaludin (Departement of Mathematics Education, 2025)
This study explores the adaptability of school principals in fulfilling leadership competencies at State Kindergartens in South Jakarta Region I. The research focuses on the transition experiences of Driving Teachers to school principals, challenges faced, and adaptation strategies implemented. Using a qualitative phenomenological approach, data was collected through interviews, observations, and documentation studies. The results indicate that the success of school principals' adaptation is influenced by leadership, social, and professional competencies. Furthermore, local contextual factors play a crucial role in the adaptation process. This study contributes to the development of educational policies related to training and mentoring school principals.